2016
DOI: 10.1177/1687814016670284
|View full text |Cite
|
Sign up to set email alerts
|

Surface grinding of carbon fiber–reinforced plastic composites using rotary ultrasonic machining: Effects of tool variables

Abstract: Carbon fiber-reinforced plastic composites have many superior properties, including low density, high strength-toweight ratio, and good durability, which make them attractive in many industries. However, due to anisotropic properties, high stiffness, and high abrasiveness of carbon fibers in carbon fiber-reinforced plastic, high cutting force, high tool wear, and high surface roughness are always caused in conventional machining processes. This article reports an investigation using rotary ultrasonic machining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The results obtained indicate that it is advisable to use the rank method instead of the Gaussian method to the competitor, which "for other results" [29] showed less accuracy in searching for common values. (11) 1.000 1.000 1.000 1.000 0.592 0.592 Differences between the media coefficients (8) and (9) also confirm the need for the second stage of the OVA. The results are the same when evaluating the cutting properties of circles relative to formulas (10) and (11).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The results obtained indicate that it is advisable to use the rank method instead of the Gaussian method to the competitor, which "for other results" [29] showed less accuracy in searching for common values. (11) 1.000 1.000 1.000 1.000 0.592 0.592 Differences between the media coefficients (8) and (9) also confirm the need for the second stage of the OVA. The results are the same when evaluating the cutting properties of circles relative to formulas (10) and (11).…”
Section: Resultsmentioning
confidence: 80%
“…It has been established that the average medians decrease, although this phenomenon occurs within the framework of the CV. This is evidenced by the median coefficients (8) and (9), which are less than one, in most cases. This, in turn, allows increasing the grinding performance while maintaining the surface quality of the parts.…”
Section: Discussionmentioning
confidence: 96%
“…drilling, grinding and electric discharge machining), rotary 1 ultrasonic machining (RUM) is an alternative machining method which is of particular interest for the machining of brittle and nonconductive materials as demonstrated in previous studies. 3,4 RUM is a hybrid machining process based on the combined material removal mechanisms of diamond grinding and ultrasonic machining resulting in higher material removal rates. The ultrasonically vibrating diamond-bonded tool is axially fed into the workpiece at a constant feed rate.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another study presented the application of RUM in surface grinding of CFRP composites. 3 The effect of rotary ultrasonic tool parameters including tool geometry, diamond abrasive size, and diamond concentration was studied on cutting force, torque, and surface roughness, and the guidelines were provided for tool selection for RUM of CFRP composites. It can be seen that in the reported studies, the performance of RUM machining process has been evaluated in terms of cutting force, material removal rate, exit chipping size, temperature generation, and tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have demonstrated that diamond abrasive tools can generate a low-damage surface with average surface roughness of about Ra 1.5 μm and higher dimensional accuracy [ 27 , 28 ]. Later, rotary ultrasonic machining produced even better surface quality with a surface roughness of about Ra 1.0 μm [ 29 , 30 , 31 ]. Other research about the machining of CFRP composites indicated that high-speed machining with spindle speeds up to 60,000–80,000 rpm could also generate good machining surface and high machining efficiency, mainly due to the remarkable reduction of cutting forces [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%